Fault-Tolerant Prescribed Performance Control of Wheeled Mobile Robots: A Mixed-Gain Adaption Approach - Zhang, Jin-Xi; Ding, Jinliang; Chai, Tianyou (IEEE transactions on automatic control, 2024)
This article is concerned with the trajectory tracking control problem for the wheeled mobile robots (WMRs) subject to actuator faults. The challenge lies in the partial loss of effectiveness of the actuated wheels which results in the loss of strong controllability of the WMR, rendering the classical fault-tolerant control methods infeasible. To overcome this obstacle, a novel mixed-gain adaption technique is put forward and is skillfully combined with the robust prescribed performance control method. The resulting control achieves trajectory tracking of the WMR with the predefined settling time and accuracy, against the actuator faults, the model uncertainties, and the disturbances. Moreover, it exhibits significant simplicity, without parameter identification, function approximation, disturbance estimation, or fault estimation. The theoretical findings are illustrated by a comparative simulation.